Railways from 1890 to 2016: a defragmented structure in braziliam history (Research, Society and Development, 2018)
Although Brazil is a continental country with a lot of land with potential for planting, Brazilian rail transport in the period from 1890 to 2016 fell short of the needs of the country and the mesh is relatively small compared to other countries that presented more economic development. The objective of the present study is to present a panorama of the historical evolution of the Brazilian railway network between 1890 and 2016. A bibliographical research of an indirect source is carried out in which one seeks to know the evolution occurred in the period. There is a period in which there is a government incentive for highways to the detriment of rail transport and, even so, evolution is occurring, in the most recent years mainly through the process of privatization of the sector and the concession of stretches to the private initiative..